The role of academic training for primary education teachers in developing teaching competencies for physical and sports education - GUERINIAI, Abdelkader; SAKHRI , Akila (sports creativity, 2025)
This study aimed to identify the role of the academic formation of primary education teachers in developing the teaching competencies of physical education and sports, as the descriptive curriculum was used for its suitability to the nature of the subject, and we relied in that on a scale as a tool for collecting information. Community in an intentional way. through this study, we reached the following results: The current study revealed that high school students have a positive role towards teaching physical education and sports, and the results also indicated the existence of positive teaching competencies towards physical education and sports.